2020
DOI: 10.3390/toxins12080511
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, Pharmacokinetics, and Concentration-QTc Analysis of Tetrodotoxin: A Randomized, Dose Escalation Study in Healthy Adults

Abstract: Tetrodotoxin (TTX) is a highly specific voltage-gated sodium channel (VGSC) blocker in clinical evaluation as a peripheral-acting analgesic for chronic pain. This study presents the first published results of the safety including cardiac liability of TTX at therapeutic-relevant concentrations in twenty-five healthy adults. Randomized, double-blind, placebo-, and positive- (moxifloxacin) controlled study evaluated single ascending doses of 15 µg, 30 µg, and 45 µg TTX over 3 periods with a 7-day washout between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Another patient in the TTX 30 µg QD cohort experienced mild QT prolongation that was unchanged from baseline ( Table S2 ). A study completed in healthy adults has demonstrated that exposure up to TTX 45 µg QD (corresponding to higher TTX plasma blood C max than 30 µg BID) does not cause blood pressure or ECG changes as determined by concentration-QTc analysis [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another patient in the TTX 30 µg QD cohort experienced mild QT prolongation that was unchanged from baseline ( Table S2 ). A study completed in healthy adults has demonstrated that exposure up to TTX 45 µg QD (corresponding to higher TTX plasma blood C max than 30 µg BID) does not cause blood pressure or ECG changes as determined by concentration-QTc analysis [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…TTX is a specific blocker of VGSCs with high affinity for TTX-sensitive VGSCs found in peripheral nerves. Like other toxins used in medicine (e.g., botulinum toxin type A, morphine, curare), therapeutic doses of TTX are safe and well-tolerated [ 38 ]. As a peripherally acting, non-addictive analgesic targeting TTX-sensitive VGSCs, TTX is a rational candidate for patients with inadequately controlled CINP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, all doses demonstrated an absence of any clinically significant toxicity. Up to 45 μg of TTX was found safe and tolerated in terms of cardiac safety [ 43 ]. Like any other toxin, TTX may present some limitations such as the low efficacy of diffusion through diverse tissue barriers to the site of action, which means that the blockage of NaV will also be limited [ 44 ].…”
Section: Toxins From Marin Animals That Target Vgscsmentioning
confidence: 99%
“…Recently, Wex Pharmaceutical Inc. has published the results of a phase 1 dose escalation study that was performed to evaluate the safety, tolerability, and pharmacokinetics of TTX at clinically relevant exposures in healthy volunteers [ 85 ]. In this randomized, double-blind, placebo-controlled study, all safety appraisals show that TTX is safe, well-tolerated, and does not cause cardiac alterations of clinical or regulatory concern or induce any clinically measurable impairment in neuromuscular or respiratory system.…”
Section: Toxicity Of Ttxmentioning
confidence: 99%